Exploring student perspectives on ChatGPT: Knowledge, attitudes, concerns, and usage patterns at Universiti Teknikal Malaysia Melaka - Md Saad, Mohd Shamsuri; Ibrahim, Ismail; Rajikon, Muhd Akmal Noor (Research and Scientific Innovation Society, 2025)
This study explores the prevalence and perspectives of ChatGPT usage among students at Universiti Teknikal Malaysia Melaka, encompassing their knowledge, attitudes, concerns, perceived ethics, and usage patterns. A total of 367 students from five faculties participated in the survey, which was conducted via Google Forms. The findings reveal a high level of awareness and familiarity with ChatGPT, with 87.2% of respondents having heard about it and 79.6% understanding its workings. However, significant concerns were identified, including the potential undermining of educational goals (mean = 3.90, SD = 0.95) and negative impacts on creative writing skills (mean = 3.46, SD = 0.91). Ethical apprehensions were also prominent, with 49.1% of students recognizing ethical or legal considerations and 64.8% expressing comfort in interacting with ChatGPT. Despite these concerns, the utility of ChatGPT in enhancing productivity and aiding academic tasks is acknowledged, evidenced by high mean scores for assistance in drafting essays (mean = 3.87, SD = 0.87) and resolving academic doubts (mean = 3.83, SD = 0.85). This study underscores the need for ethical guidelines and controlled integration of ChatGPT into educational practices to balance its benefits with the maintenance of academic integrity and critical thinking skills.